Assessment of gestational diabetes mellitus knowledge, attitudes, and practices and associated factors among pregnant women at a district hospital in Coastal Kenya - Nanyangwe Siuluta; Miho Sato; Le Khac Linh; Violet Wanjihia; Mwatasa Salim Changoma; Nguyen Tien Huy; Satoshi Kaneko (Tropical Medicine and Health)
Abstract Background Gestational diabetes mellitus (GDM) is any degree of glucose intolerance first recognized during pregnancy. GDM awareness among pregnant women translates into GDM prevention and early diagnosis. Objective To establish the underlying factors influencing GDM Knowledge Attitude and Practices (KAP) among pregnant women at Kinango District Hospital. Method An explanatory mixed-methods design was implemented by initially assessing GDM KAP quantitatively [QUAN], followed by the qualitative [qual] exploration of contextual factors behind quantitative results. In the [QUAN] strand, 354 pregnant women were interviewed from January to February 2019. Thereafter, in the [qual] strand, key informant interviews were conducted among four pregnant women and three healthcare workers; a focus group discussion was held among nine pregnant women, from May to June 2019. STATA V15 software package was used to analyze the quantitative data. Qualitative data were analyzed manually using thematic analysis. Result Among 354 pregnant women, 29.0% were knowledgeable, 46.98% had good attitude and 60.17% had good practice. Attending at least one antenatal clinic visit and having heard about diabetes mellitus were associated with good GDM attitude and practices. Among the knowledgeable pregnant women, one-third (33.33%) obtained GDM information from a health facility. Discussions with pregnant women and the interviews with healthcare workers highlighted that daily health talks during antenatal clinic, included GDM and diabetes mellitus information. Furthermore, attendance of at least one antenatal clinic visit was low (85.88%), among pregnant women (87.86%) who were expected to have attended at least one antenatal clinic visits. Conclusion Despite low GDM knowledge, pregnant women had relatively good GDM attitudes and good GDM practices. Daily health talks conducted during antenatal clinic as well as indigenous knowledge among pregnant women, influenced the latter. Hence, GDM information dissemination needs to be enhanced for the improvement of GDM KAP among pregnant women for GDM prevention.